2019
DOI: 10.1080/00758914.2019.1664197
|View full text |Cite
|
Sign up to set email alerts
|

The petrography of imported Levantine Combed vessels from early Old Kingdom Giza

Abstract: Thin-section petrography was used to examine 36 samples of imported Early Bronze Age Combed vessels from Giza, Egypt. The samples come from fragmentary pots found in early Old Kingdom tombs of high officials, and the workers' settlement at Heit el-Ghurab. Most date to the 4th Dynasty; coeval with the ARCANE Early Central Levant (ECL) 4 and Early Southern Levant (ESL) 5b periods. Results reveal a primary fabric with slight variations, containing material pointing to production centres close to Cretaceous format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Although based on a few reliable samples, the age models (G1 and G4) were supported by pottery sherds found in the sedimentary deposits. The samples are dated to the Predynastic and Early Dynastic-Old Kingdom periods by comparison with earlier studies at Giza ( 46 ) and Saqqara ( 47 ). The age-models are also corroborated by comparison with high-resolution sequences such as Lake Tana ( 21 ) ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Although based on a few reliable samples, the age models (G1 and G4) were supported by pottery sherds found in the sedimentary deposits. The samples are dated to the Predynastic and Early Dynastic-Old Kingdom periods by comparison with earlier studies at Giza ( 46 ) and Saqqara ( 47 ). The age-models are also corroborated by comparison with high-resolution sequences such as Lake Tana ( 21 ) ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Ceramic studies have suggested that wine and olive oil were among the materials that were imported into Egypt from the Levant, likely already starting from the end of the fourth millennium and then developing throughout the third millennium with the entire Levant being involved in the exchanges. Principle economic partners changed through time, with most of the materials likely being imported first from the Southern Levant, while later the Central and Northern Levant assumed a privileged role [95][96][97][98][99][100]. These developments likely contributed to supporting the increasing social stratification, which becomes already evident in the urbanization processes during the first half of the third millennium.…”
Section: Increased Social Stratification In the 4 Th Millennium Bc Le...mentioning
confidence: 99%